2022
DOI: 10.1590/pboci.2022.028
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antiadhesion Effects of Psidium guajava Fractions on a Multispecies Biofilm Associated with Periodontitis

Abstract: Objective: To assess the antibacterial activity of Psidium guajava fractions and their effects on adhesion of a multispecies biofilm consisting of Streptococcus gordonii, Fusobacterium nucleatum, and Porphyromonas gingivalis in vitro. Material and Methods: Guava leaves were obtained from the mountains of northern Peru, where they grow wild and free of pesticides. The antimicrobial activity of 25 mg/mL petroleum ether, 25 mg/mL dichloromethane and 25 mg/mL methanol fractions of P. guajava was evaluated by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…During the last decade, P. guajava leaves have been widely investigated for their antimicrobial potential including bactericidal and/or anti-biofilm activities against various pathogenic bacteria. For instance, the methanol fraction of P. guajava leaves from Peru had an antibacterial effect on Streptococcus gordonii and Porphyromonas gingivalis , and, at the relatively high concentration of 1.56 mg/mL, decreased biofilm adhesion [ 20 ]. Similarly, Dutta et al [ 21 ] demonstrated anti-biofilm activities of leaves methanol extracts, from which benzyl isocyanate, at the concentration of 440 µg/mL, appeared as a major anti-biofilm compound against Staphylococcus aureus clinical strains.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, P. guajava leaves have been widely investigated for their antimicrobial potential including bactericidal and/or anti-biofilm activities against various pathogenic bacteria. For instance, the methanol fraction of P. guajava leaves from Peru had an antibacterial effect on Streptococcus gordonii and Porphyromonas gingivalis , and, at the relatively high concentration of 1.56 mg/mL, decreased biofilm adhesion [ 20 ]. Similarly, Dutta et al [ 21 ] demonstrated anti-biofilm activities of leaves methanol extracts, from which benzyl isocyanate, at the concentration of 440 µg/mL, appeared as a major anti-biofilm compound against Staphylococcus aureus clinical strains.…”
Section: Introductionmentioning
confidence: 99%